Excess Thermodynamic Properties of Mixtures Involving Xenon and Light Alkanes: A Study of Their Temperature Dependence by Computer Simulation - Martins, Luís F. G. (2012)
As a natural extension of a previous work, excess molar enthalpies and excess molar volumes as a function of composition in a wide range of temperatures have been obtained for binary mixtures of xenon with ethane, propane, and n-butane by Monte Carlo computer simulation. Xenon was modeled by a simple spherical Lennard-Jones potential, and the TraPPE-UA force field was used to describe the n-alkanes. One of the main goals of this study is to investigate the temperature dependence of the excess properties for mixtures of xenon and n-alkanes and, if possible, to supplement the lack of experimental data. For all three systems, the simulation results predicted excess volumes in good agreement with the experimental data. As for the excess enthalpies, in the case of (xenon + ethane), the simulation results confirm the negative experimental result and the weak temperature dependence. In the case of (xenon + propane) and (xenon + n-butane), however, the simulation predicts negative excess enthalpies, but those estimated from experimental data are positive. Both excess volumes and enthalpies display a complex dependence on temperature that in some aspects resembles that found for mixtures of n-alkanes.The structure of the liquid mixtures was also investigated by calculating radial distribution functions [gαβ(r)] between each pair of interaction groups for all the binary systems at all temperatures. It is found that the mean distance between xenon and CH2 groups is systematically higher than the distance between xenon and CH3. In addition, the number of groups around xenon in the first coordination sphere was calculated and seems to be proportionally more populated by methyl groups than by methylene groups. The results seem to reflect a preferential and stronger interaction between xenon and CH3, in agreement with previous findings.